Innovation policy for SMEs proves successful - Heike Belitz; Alexander Eikelpasch; Anna Lejpras (DIW Economic Bulletin, 2013)
The innovation policy of the German government and Länder provides small and medium-sized enterprises (SMEs) with a wide range of programs to promote their research and development (R&D) and focuses, in particular, on the transfer of knowledge. In recent years, the programs have been streamlined and funding substantially increased as part of the second economic stimulus package. SMEs have profited from this: the number of research performing SMEs has grown; they have increased their R&D expenditure and intensified their knowledge exchange with universities and research centers. Technology-neutral government funding is to remain at the current level-around ten percent of SMEs' R&D expenditure-thus providing more targeted support for knowledge transfer.
Keywords: O14; O25; O38; 330; R&D; small and medium-sized enterprises; technology and innovation policy